Prediction of Surgical Staging in Patients with Low-Risk Endometrial Cancer Using Intraoperative Assessment of Myometrial Invasion and Preoperative Tumor Grading - Yanaranop, Marut; Tuipae, Suphet (Thai Journal of Obstetrics and Gynaecology, 2012)
Objectives: To assess the benefit of intraoperative gross depth of myometrial invasion and preoperative grading as a predictor of final surgical staging in patients with low-risk endometrial cancer. Materials and Methods: Retrospective chart review of all patients with endometrial cancer underwent surgery at Rajavithi Hospital from January 1st, 2002 to December 31st, 2006 for demographic and clinical data, preoperative tumor grading, intraoperative gross depth of invasion and final surgical staging. Results: A total of 124 patients were eligible for analysis using data on intraoperative assessment of gross depth of myometrial invasion (no myometrial invasion or myometrial invasion less than 50%) and preoperative curettage/biopsy (grade 1 and 2). The intraoperative gross depth of myometrial invasion was upgraded 35.5% and discrepant 42.7% compared with pathologic myometrial invasion, whereas the preoperative tumor grading was upgraded 19.4% and discrepant 28.2% compared with final tumor grading. The predictive staging was clinically significantly upstaged 28 %, 30%, 33.3% and 21.4% of stage IAG1, IAG2, IBG1 and IBG2, respectively. Predictive staging resulted in suboptimal surgical treatment in 30.6% by relinquishment of lymphadenectomy. Conclusion: The combination of preoperative tumor grading and intraoperative gross depth of myometrial invasion is the poor predictor for final staging.